Screening for microbial inhibitors particularly against the glyoxylate pathway in Mycobacterium - Sylvia Daim (2003)
The focus of this study was to attempt to find strain of soil microbes from the biodiversity of Sabah that is able to produce structurally novel compound with inhibitory activity against the Mycobacterium tuberculosis ICL. Isolation of soil microbes from soil was conducted and a total of 44 strains of actinomycetes were isolated from the soil samples collected from lmbak Valley and Tabin Conservation Area. The isolated actinomycetes strains were grown aerobically for the production of secondary metabolites, which were extracted using acetone. A total of 582 different crude acetone extracts were screened: 277 were extracts of filamentous fungi, 113 were extracts of mangrove actinomycetes strains, 77 were extracts of actinomycetes strains isolated in this study and 115 were extracts of actinomycetes strains isolated from the rain forests. The crude acetone extract of the actinomycetes strain H7763, isolated in this study was found with the most promising ICL inhibitory activity. Detailed study of the crude acetone extract of strain H7763 found that peptone water (Merck cat. 1.07228) and soybean flour (Sigma cat. S-9633) were the more suitable organic nitrogen sources for the promotion of the synthesis of the potential ICL inhibitor by strain H7763. When grown at the growth conditions established in this study, the potential ICL inhibitory activity can be reliably reproduced. The potential ICL inhibitory activity showed concentration dependence; diameters of inhibition zones increased with increasing volume of the extract tested. The crude acetone extract of strain H7763 were also found to be toxic to Bacillus subtilis, Escherichia coli, Staphylococcus aureus and Mel Mycobacterium smegmatis. In addition, the extract of strain H7763 also inhibited the two target organisms of the ICL screening system, the ic/-transformant and the wild type M. smegmatis when grown on Tween-80 minimal medium agar. ltaconic acid, a known competitive inhibitor of various ICL was able to inhibit the growth of the the ic/-transformant and the wild type M. smegmatis when grown on either glucose or acetate or Tween-80 minimal medium. An unexpected discovery was made of the crude acetone extract of the actinomycetes strain H7372, which was characterized as no-activity in the first screen. The extract showed weak inhibitory activjty both on the glucose and the acetate minimal medium, but strong inhibitory activity on the Tween-BO minimal medium. In this study, in vitro cell-free ICL enzymatic spectrophotometric assay failed to provide conclusive evidence of the ICL inhibitory potential present in the crude acetone extract of strain H7763. Morphology description conducted for the actinomycetes strain H7763 showed that it is likely a species of the genus Streptomyces. Spores were formed in chains that were spiral in shape, and the cell wall contained LL-DAP isomer. At the conclusion of this study, the ICL inhibitory potential of the bioactive compound produced by the actinomycetes strain H7763 remained to be tested.